A rare case of fatal sepsis caused by Trichosporon asahii in an immunocompetent chronic obstructive pulmonary disease patient - M, Shamshuzoha; Menon, Indira; H, Sowjanya (Indian Journal of Case Reports, 2024)
Trichosporon asahii is an yeast-like organism that is emerging as an important cause of invasive fungal infection in immunocompromised patients, especially in patients with cancer and neutropenia. Invasive infections due to T.asahii in immunocompetent patients are rarely reported.  We describe a 62-year-old COPD (chronic obstructive pulmonary disease) patient who contracted severe sepsis from T.asahii without any prior history of immunosuppression. He was successfully treated with voriconazole and was discharged from the hospital.